Der zerbrochene Kopf : Picasso zum 100. Geburtstag. (Hamburg : Hamburger Kunsthalle, 1981)
Archipenko, Alexander ; Barlach, Ernst ; Brancusi, Constantin ; Braque, Georges ; Chagall, Marc ; Corinth, Lovis ; Delaunay-Terk, Sonia ; Derain, André ; Despiau, Charles ; Heckel, Erich ; Hodler, Ferdinand ; Klimt, Gustav ; Kollwitz, Käthe ; Kokoschka, Oskar ; Mondrian, Piet ; Picasso, Pablo ; etc.
Der zerbrochene Kopf : Picasso zum 100. Geburtstag, Hamburger Kunsthalle, Hamburg, 11. Dezember 1981 bis 21. Februar 1982
boek